1998
DOI: 10.1524/ract.1998.82.special-issue.399
|View full text |Cite
|
Sign up to set email alerts
|

Probability of Production of Mobile Plutonium in Environments of Soil and Sediment

Abstract: Mobile plutonium was found in the bottom sediment in the Nishiyama reservoir in Nagasaki after more than 40 years from deposition of local fallout released in the explosion of the ABomb in 1945. Less than 10% of total deposited plutonium had turned into a mobile form in the bottom environment of the reservoir. The environmental conditions at bottom sediment is expected to be rich organic materials and high bacterial population under anaerobic conditions. Anaerobic bacteria have a high ability to uptake plutoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The increasing level of biological activity from April to August, which appears to retard the aqueous-phase concentrations of Pu and Am comparably, is therefore consistent with a bioaccumulation mechanism. This is in agreement with Mahara and Kudo (15), who suggested that Pu was retained by living bacterial cells in sediment environments. The transuranic aqueous-phase concentrations patterns observed in the earlier part of the year do not correspond to any change in activity/biomass or in community structure.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The increasing level of biological activity from April to August, which appears to retard the aqueous-phase concentrations of Pu and Am comparably, is therefore consistent with a bioaccumulation mechanism. This is in agreement with Mahara and Kudo (15), who suggested that Pu was retained by living bacterial cells in sediment environments. The transuranic aqueous-phase concentrations patterns observed in the earlier part of the year do not correspond to any change in activity/biomass or in community structure.…”
Section: Discussionsupporting
confidence: 93%
“…However, Pu(V) equally could be used as an electron acceptor in microbial respiration in a similar way to that demonstrated for U(VI) by Lovley et al (14), so its reduction and loss from solution could be directly related to microbial activity. Alternatively, the increase in microbial biomass during the summer could provide a sink for the Pu, which could then be released in a more mobile form as the cells degrade in the winter (15). In this study we investigate the cycling of Pu further, broadening the scope of the study to include the two other major transuranium elements, Np and Am.…”
Section: Introductionmentioning
confidence: 99%
“…For Pu, particle sizes of intrinsic colloids vary from < 1 nm to > 15 μm (Ichikawa and Sato, 1984; Kim et al, 1985). Finally, Pu can also associate with biocolloids such as bacteria (Mahara and Kudo, 1998; Mahara and Kudo, 2001). The model depicted in Fig.…”
Section: Conceptual Models For Colloid‐facilitated Contaminant Transpmentioning
confidence: 99%